2023
DOI: 10.3961/jpmph.22.388
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Stunting Among Under-5 Children in Rwanda Using Machine Learning Techniques

Abstract: Objectives: Rwanda reported a stunting rate of 33% in 2020, decreasing from 38% in 2015; however, stunting remains an issue. Globally, child deaths from malnutrition stand at 45%. The best options for the early detection and treatment of stunting should be made a community policy priority, and health services remain an issue. Hence, this research aimed to develop a model for predicting stunting in Rwandan children.Methods: The Rwanda Demographic and Health Survey 2019-2020 was used as secondary data. Stratifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…32 Being at higher altitudes is associated with a high risk of stunting in children in Rwanda as revealed by the study. 11 It is crucial to emphasise that altitude is only one of several factors that contribute to stunting, and its influence varies depending on other contextual factors such as economic status, healthcare facilities, and dietary choices. 33 To alleviate stunting in high-altitude locations, a comprehensive approach is required, which includes increasing access to healthcare, nutrition, sanitation, and education, as well as addressing the underlying socioeconomic determinants of health, 34 this study also confirm the findings shown in the different studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Being at higher altitudes is associated with a high risk of stunting in children in Rwanda as revealed by the study. 11 It is crucial to emphasise that altitude is only one of several factors that contribute to stunting, and its influence varies depending on other contextual factors such as economic status, healthcare facilities, and dietary choices. 33 To alleviate stunting in high-altitude locations, a comprehensive approach is required, which includes increasing access to healthcare, nutrition, sanitation, and education, as well as addressing the underlying socioeconomic determinants of health, 34 this study also confirm the findings shown in the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…10 A few studies have been conducted in Rwanda using other machine learning technics like logistic regression, Supportive Vector Machine (SVM), Naive Bayes Random Forest (RF), XGBoost gradient model. 11 However, based on the existing knowledge there has been few researches in Rwanda that attempted to utilise ML to predict stunting like the study conducted by Similien et al 11 ANNs have proven to be highly effective in predicting illnesses. However, Similien's publication did not delve into the utilisation of ANNs for this purpose, despite their demonstrated effectiveness in prediction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper in [276] employs a machine learning approach to predict the demand for essential medicines in Rwanda based on consumption data. The research outlined in [277] utilizes machine learning techniques for predicting stunting among under-5 children in Rwanda. [278] explores the early detection of students at risk of poor performance in Rwanda's higher education using machine learning techniques.…”
Section: K Rwanda 1) Researchmentioning
confidence: 99%
“…The contribution of this study is to propose an ML model that performs better for stunting detection (Ndagijimana et al 2023). This ML model includes algorithm selection, oversampling, feature selection, feature weighting, data distribution, and determining algorithm parameters (Sultana and Islam 2023).…”
Section: Introductionmentioning
confidence: 99%